The Murder House Case Studies: An Education in Dental Anxiety - Cartwright, Susan Helen (Auckland University of Technology, 2010)
Dental anxiety levels have not declined as expected with the advent of relatively pain-free dental treatment, and this anxiety can lead to poor dental health. Investigation of its causes is necessary along with methods to moderate it. The New Zealand context is unique as the school dental service model was pioneered in this country and memories of childhood treatment at these clinics in the mid 20th century have impacted on some adults’ ability to cope with dental treatment today. A questionnaire based survey revealed that dental anxiety in a population of university staff members was extreme in 12-16%, and development of this anxiety was often attributed to treatment experiences associated with the school dental clinic, also referred to as the “murder house”. Nine case studies were compiled drawing on background information from the survey and in depth semi-structured interviews. Murder house stories that told of such things as cold, sterile clinics, unsympathetic practitioners, and treadle drills, were defined and the causes of anxiety were discussed with reference to a broad range of literature. A model for dental anxiety was developed based on the case study findings and a further model illustrating the theoretical basis for the development and maintenance of anxiety was constructed after consideration of the data in light of classical conditioning, social learning and attribution theories. Implications of these findings for an oral health programme curriculum and pedagogy were then considered. Suggestions for interventions which practitioners could use to assist anxious dental patients were made including, educational methods such as modelling behaviour and informative education along with coping strategies, and narrative and cognitive- behavioural therapies. Social marketing was proposed as a way to combat the effects of negativity in society and the media. Further investigation of the efficacy of the intervention methods presented, and those measures already in place, to reduce dental anxiety is warranted along with the assessment of the potential value of the educational models suggested for use with dental and allied students and practitioners.
Keywords: Anxiety; Dental